Skeletal Muscle Metabolism: Origin or Prognostic Factor for Amyotrophic Lateral Sclerosis (ALS) Development? - Cyril Quessada; Alexandra Bouscary; Frédérique René; Cristiana Valle; Alberto Ferri; Shyuan T. Ngo; Jean-Philippe Loeffler (Cells, 2021)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by progressive and selective loss of motor neurons, amyotrophy and skeletal muscle paralysis usually leading to death due to respiratory failure. While generally considered an intrinsic motor neuron disease, data obtained in recent years, including our own, suggest that motor neuron protection is not sufficient to counter the disease. The dismantling of the neuromuscular junction is closely linked to chronic energy deficit found throughout the body. Metabolic (hypermetabolism and dyslipidemia) and mitochondrial alterations described in patients and murine models of ALS are associated with the development and progression of disease pathology and they appear long before motor neurons die. It is clear that these metabolic changes participate in the pathology of the disease. In this review, we summarize these changes seen throughout the course of the disease, and the subsequent impact of glucose–fatty acid oxidation imbalance on disease progression. We also highlight studies that show that correcting this loss of metabolic flexibility should now be considered a major goal for the treatment of ALS.